KINETIC STUDY OF THE REACTION OF 2,2’-BIPYRIDYL CHROMIUM PEROXIDE WITH ALCOHOLS (Journal of Sciences, Islamic Republic of Iran)
The rate constants and activation parameters are reported for the oxidation of methanol, ethanol, propanol, and isopropanol by 2,2’-bipyridyl chromium peroxide (BPCP) over the temperature range of 35° to 50°C.